Assessment of Agronomic Zinc Biofortification of Alley Cropped Pearl Millet - Verma, Kamlesh; Prasad, Saroj Kumar; Singh , Manoj Kumar; Sharma , Prashant (Bangladesh Journal of Botany, 2023)
The availability of nitrogen (N) and zinc (Zn) at the specific plant growth stage is crucial for attaining the higher nutrient use efficiency (NUE) and uptake. An experiment was conducted, having 4-N scheduling [No N; ½[basal]+ ½[3rd visible leaf (VL)]; ¼[basal]+ ½[3rdVL]+ ¼[panicle extended in flag leaf sheath (PEFLS)]; ½[basal] + ¼[3rdVL]+ ¼[panicle visible (PV)], and 4-Zn scheduling [No Zn; 2.5 kg/ha [basal]+ 0.25% spray(*) [panicle initiation (PI)]; 2.5 kg/ha [basal]+0.25% [PI]*+ 0.25% [PEFLS]*; 2.5 kg/ha [basal]+ 0.25% [50% panicle emergence (PE)]*+ 0.25% [milk stage (MS)]*. Nitrogen schedule at ¼[basal]+ ½[3rdVL]+ ¼[PEFLS] recorded the maximum nutrient content, uptake, and NUE. Similarly, the maximum nutrient content, uptake, and nutrient use efficiency observed in the Zn at 2.5 kg/ha [basal]+0.25% [PI]*+ 0.25% [PEFLS]*. Moreover, N and Zn interacted significantly to increase the grain N and Zn content and uptake by grain. Bangladesh J. Bot. 52(1): 203-209, 2023 (March)